(untitled) (International Seven Journal of Multidisciplinary, 2025)
The increase in life expectancy in Brazil and worldwide has required greater use of new approaches in medicine, including the expansion of the availability of previously existing demands, with particular emphasis on the role of palliative care (PC). This article aimed to summarize a previously published paper in the Revista Brasileira de Medicina de Família e Comunidade, which characterized the PC practices carried out by family and community physicians (FCP) in Brazilian PHC, according to the domains of the National Consensus Project for Quality Palliative Care. PC practices in PHC were shown to be limited by training gaps, low availability of qualified teams, difficulties accessing opioids, and insufficient approaches to psychosocial and communication aspects. It was concluded that the provision of PC in Brazilian PHC is restricted and depends not only on the competencies of FCPs but also on public policies that enable a structured multidisciplinary practice. Further studies are needed to deepen and compare these findings, as well as promote the strengthening of PC within the scope of PHC in the country.